2015
DOI: 10.1111/aogs.12718
|View full text |Cite
|
Sign up to set email alerts
|

Guideline‐based development of quality indicators for prevention and management of postpartum hemorrhage

Abstract: This study describes a stepwise systematic development of 22 performance and organizational indicators to use for measuring the whole care process of prevention and management of PPH.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
24
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 21 publications
(24 citation statements)
references
References 46 publications
0
24
0
Order By: Relevance
“…The structure of the interview was based on previously developed quality indicators and the two theoretical frameworks. The quality indicators, which were based on PPH-guidelines and ATLS-based course instructions, consisted of the following five domains: 1) Prevention of PPH, 2) Management of patients with >500 ml blood loss, 3) Management of patients with >1000 ml blood loss or with signs of shock and 4) Organisation of PPH-care and 5) Management of patients with >2000 ml blood loss [ 27 ]. All participants were asked to mention obstacles and facilitators for providing high quality care on the subjects of the first four domains, particularly regarding adherence to evidence-based guidelines and ATLS-based course instructions.…”
Section: Methodsmentioning
confidence: 99%
“…The structure of the interview was based on previously developed quality indicators and the two theoretical frameworks. The quality indicators, which were based on PPH-guidelines and ATLS-based course instructions, consisted of the following five domains: 1) Prevention of PPH, 2) Management of patients with >500 ml blood loss, 3) Management of patients with >1000 ml blood loss or with signs of shock and 4) Organisation of PPH-care and 5) Management of patients with >2000 ml blood loss [ 27 ]. All participants were asked to mention obstacles and facilitators for providing high quality care on the subjects of the first four domains, particularly regarding adherence to evidence-based guidelines and ATLS-based course instructions.…”
Section: Methodsmentioning
confidence: 99%
“…But some problems could not be overlooked, gestational hypertension, preeclampsia, heart disease, glaucoma, asthma and drug hypersensitivity were uterotonic contraindications, and drug life-time limits its repeated usage in a short time, uterotonics also brought side effect like nausea, vomiting, diarrhea, headache and increased blood pressure [8] , a systematic review in 2015 even found no satisfactory evidence could suggest what kind of uterotonic was the most effective for uterine atony [18] . Two previous studies mentioned so-called clamp for xing intrauterine balloon, or recommending Bilateral Cervix Apex Clamping (BCAC) procedure as a noninvasive therapy for severe postpartum hemorrhage [11,19] , both operations were completely different from bilateral-contralateral cervix clamp we proposed. The present study found this new technique could effectively reduce blood loss at third stage of labor or after vaginal/caesarean birth, and it was much safer than uterotonics.…”
Section: Discussionmentioning
confidence: 97%
“…In our study, there were three merits of using the TSCLB to measure the amount of blood loss in vaginal delivery. First, it was extremely di cult to measure the actual amount of blood loss by visual estimation methods, because blood and amniotic uid are often mixed during childbirth [23]. We designed the new TSLCB for vaginal delivery, which allowed the blood to be separated from the amniotic uid by collecting the components in two transparent plastic bags.…”
Section: Discussionmentioning
confidence: 99%